Cetacean presence and distribution and relationship with environmental and anthropogenic parameters in central western Mediterranean Sea, using data from network of fixed sampling transects using ferry as platform of research - Arcangeli, Antonella (Università degli studi Roma Tre, 2016)
During the summers of 2010 and 2011, weekly cetacean surveys were undertaken in “passing mode”, using ferries as platforms of opportunity, along the “fixed line transect” between Catania and Civitavecchia (southern Italy). Of the 20 species of cetaceans confirmed for the Mediterranean Sea, eight were sighted within the survey period, of which seven species represented by Mediterranean subpopulations (Balaenoptera physalus, Physeter macrocephalus, Stenella coeruleoalba, Delphinus delphis, Grampus griseus, Tursiops truncatus and Ziphius cavirostris) and one is considered a visitor (Steno bredanensis). A total of 220 sightings were effected during 2010 and a total of 240 sightings in 2011. The most frequently recorded species was S. coeruleoalba. By the comparing the data from the two sampling seasons, a significant increase of D. delphis sightings and a decrease of sightings of B. physalus and P. macrocephalus were observed. While all the other species were observed in both sampling seasons, Z. cavirostris and Steno bredanensis were observed only during 2011. The presence of mixed groups of odontocetes was also documented: groups composed of pairs of species were S. coeruleoalba and D. delphis, S. coeruleoalba and T. truncatus, and S. coeruleoalba and G. griseus. The results of this research add useful information on cetacean species in a very poorly known area and highlight the need to standardize large-scale and long-term monitoring programs in order to detect variation in presence, abundance and distribution of cetaceans populations and understand the effect of anthropogenic factors.